Infrared thermography as a tool for measuring water stress index in avocado cultivars (Persea americana M.) - Ramos-Fernández, Lia; Galindo-Sánchez, Malú Massiel; Núñez-Alfaro, Herbert; Espinoza-Núñez, Erick; Pino-Vargas, Edwin; del Águila-Ríos, Sandra (Agronomía Mesoamericana, 2024)
Introduction. Avocado cultivation is susceptible to water stress during the flowering stage and initial fruit growth. This stress can cause premature fruit drop and accentuate the alternation in production. Objective. To determine the water stress index of the crop (CWSI) in three avocado cultivars (Hass, Fuerte, and Zutano) under different irrigation conditions, using infrared thermography. Materials and methods. The study was carried out in the autumn season of 2023, at the Canaán Agricultural Experimental Station, Ayacucho, Peru. A total of 170 four-year-old avocado trees in the reproductive phase were selected. Five evaluations were carried out under different irrigation conditions, where information was collected after 14 and 7 days without irrigation (WI-14d and WI-7d) and 12, 2, and 1 hour after irrigation (AI-12h, AI-2h, and AI-1h, respectively). Leaf temperature (Th), stomatal conductance (gs), soil moisture (θ), and CWSI were recorded. Results. The three cultivars evaluated in this study showed significant differences in Th according to irrigation management. These variations, influenced by environmental temperature and humidity, established stress thresholds that defined the CWSI in a range from 0.34 to 0.96. When relating the CWSI with gs and θ, an R of 0.51 and 0.61 was obtained respectively. The Zutano cultivar showed the highest CWSI value in prolonged periods of irrigation restriction, but had a low capacity to reduce these values after rehydration, unlike the other cultivars. Conclusions. Infrared thermography is a crucial tool for assessing the water status and responses of avocado cultivars to different irrigation and environmental conditions, with Th and CWSI as indicators that respond to environmental conditions.